2018
DOI: 10.1029/2018rg000624
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic Slope Current in a Changing Climate

Abstract: The Antarctic Slope Current (ASC) is a coherent circulation feature that rings the Antarctic continental shelf and regulates the flow of water toward the Antarctic coastline. The structure and variability of the ASC influences key processes near the Antarctic coastline that have global implications, such as the melting of Antarctic ice shelves and water mass formation that determines the strength of the global overturning circulation. Recent theoretical, modeling, and observational advances have revealed new d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
385
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(411 citation statements)
references
References 230 publications
(460 reference statements)
26
385
0
Order By: Relevance
“…Moffat et al (2008) discussed the dynamics of buoyancy-driven coastal currents and their dependence on the seasonal modulation of melt rate. Much of this freshwater input at the Ross Sea's eastern boundary past Cape Colbeck flows along the continental slope in the Antarctic Slope Current (Thompson et al, 2018); however, some turns southward into Little America Basin toward the eastern Ross Ice Shelf front (Orsi & Wiederwohl, 2009, their Figure 5b). Realistic numerical model simulations (Dinniman et al, 2015;Kusahara & Hasumi, 2014;Nakayama et al, 2014) also demonstrate this freshwater pathway.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Moffat et al (2008) discussed the dynamics of buoyancy-driven coastal currents and their dependence on the seasonal modulation of melt rate. Much of this freshwater input at the Ross Sea's eastern boundary past Cape Colbeck flows along the continental slope in the Antarctic Slope Current (Thompson et al, 2018); however, some turns southward into Little America Basin toward the eastern Ross Ice Shelf front (Orsi & Wiederwohl, 2009, their Figure 5b). Realistic numerical model simulations (Dinniman et al, 2015;Kusahara & Hasumi, 2014;Nakayama et al, 2014) also demonstrate this freshwater pathway.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Interaction between currents on the upper continental slope and troughs at the shelf break promotes MCDW intrusions onto the continental shelf (e.g., Dinniman et al, ; Jenkins et al, ; Palóczy et al, ; St‐Laurent et al, ). Easterly winds drive a westward current along most of the Antarctic slope, known as the Antarctic Slope Current (Thompson et al, ). The Antarctic Slope Current transports MCDW, and it is diverted poleward along isobaths when it encounters a trough, resulting in intrusions originating from the east of a trough (Klinck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Antarctic Slope front (ASF) acts as a strong dynamical barrier to the inflow of CDW across the shelf in East Antarctica (Spence et al, ; Thompson et al, ), intrusions of mCDW have been observed in the sea ice growth season (March–August), entering Prydz Bay over Four Ladies Bank (FLB) and occupying the eastern side of the bay following the cyclonic PBG and are directed toward the eastern flank of the AIS (Herraiz‐Borreguero et al, ; Liu et al, ; Williams et al, ). The interaction of the AIS with mCDW heat transport has been clarified by several studies (Herraiz‐Borreguero et al, , ; Wong et al, ), and the AIS net basal melt rate driven by mCDW inflow was estimated at 1.0 ± 0.4 m/year (Herraiz‐Borreguero et al, ), reducing local shelf water density and suppressing its potential contribution to AABW formation (Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%